Time Cost Trade-Off Problem Using Intuitionistic Fuzzy with Real Time Application in the Field of Construction - S, Priyadharshini; G, Deepa (Contemporary Mathematics, 2024)
In order to assist in locating the critical path in an acyclic network, the Critical Path Method (CPM) employs intuitionistic triangular fuzzy number. Project crashing is a technique used to cut the project timeline fast by minimizing the duration of one or more critical task below their typical duration. The goal of crashing, often referred to as the time-cost trade-off, is to shorten the project’s duration while lowering its cost. The intuitionistic fuzzy critical path technique and the time-cost trade-off issue were developed as a result of the uncertainty or ambiguity around the length of activities. The present investigation proposes an optimal method for handling the time-cost trade-off problem (TCTP). When the duration aspect is taken into account, the project’s overall cost is effectively reduced. It is simpler to compute the time and monetary expenses of being on the critical path while using this approach. An existing application from the literature is selected and implemented to demonstrate the operation of this technology. Additionally, we suggested a ranking method for defuzzification called “Magnitude measure”. Both the traditional approach and the path length ranking methodology are used for verification. MATLAB is used to give simulation results.